Cloudlet–screen computing: a client–server architecture with top graphics performance. (30th May 2013) - Lin, Tao; Zhou, Kailun; Wang, Shuhui
This paper presents a three–decoupling–boundary theory and classification for performance analysis of client–server architectures. Based on the analysis, a novel client–server architecture with top graphics performance is proposed. The client is only a display screen plus a few Human–Interface–Devices such as a mouse–keyboard–set or touchscreen with an optional mobile storage. The client is connected to a remote or nearby server (cloudlet) by a low latency link transferring primarily post–GPU display screen and HID data. By following exactly the same most–efficient CPU–GPU–screen graphics rendering pipeline from initial graphics primitives to final pixels as that in the traditional computer graphics architecture developed and optimised in the past decades, the architecture has higher graphics and multimedia performance than any other client–server and cloud–mobile computing architectures, e.g. VNC, Remote Desktop, VDI, Zero–client, and PCoIP. No read back of frame buffers as virtualised screen is necessary, so no CPU/GPU overhead occurs and display latency is minimised.